Implementation of The Fuzzy Tsukamoto Method for Office Stationery Estimation Stock System - Tedy Rukmana; Hersanto Fajri; Dahlia Widhyaestoeti (Kresnamedia Publisher, 2022)
Information technology supports the company's operational activities in recording incoming goods, outgoing goods, and existing inventory. PT. Mitraniaga Distribusindo is a company engaged in food distribution, which includes supporting aspects for smooth operations, such as stock availability of office stationery. The Tsukamoto fuzzy method aims to calculate the estimated stock of office stationery needed to provide recommendations for deciding the estimated stock. The estimated target variable is more numerical, with models built using complete records providing the variable value of the target as a predictive value. Testing the accuracy of the calculation results of the office stationery stock estimation system was conducted using the Root Mean Squared Error (RMSE) to get a value of 5.9 to make the decisions more precise. In application development, using the waterfall model, which provides a sequential or sequential software life flow approach starting from design analysis, coding, and up to application testing using black box testing that is produced, each test form produces an appropriate status, according to the expected results.